NF-kappaB function and activation in mouse mammary stem cells and its interplay with the downstream target, cIAP2 in MMTV-ErbB2 induced tumourigenesis - Hurst, Kathleen M (University of Ottawa (Canada), 2010)
The process of tumourigenesis in breast cancer involves a number of cellular proteins that work in concert to allow for cellular survival, proliferation, angiogenesis and continued tumour growth. The transcription factor NF-kappaB, which is often constitutively expressed in mammary carcinoma, signals through a number of downstream targets, one of which is cIAP2, to promote cellular growth and evasion of apoptosis. It is unclear if the NF-kappaB in cancer is needed for mammary stem cell or tumour-initiating cell survival. In the first part of this two-part study, it was shown that MMTV-ErbB2 mice lacking cIAP2 expression developed tumours with increased latency compared to MMTV-ErbB2 mice with cIAP2 expression. These tumours exhibited no change in cellular mitotic index or levels of tumour-associated macrophage infiltration, but did exhibit an increase in the number of apoptotic cells and an increase in angiogenesis. Preliminary data also suggests that tumours in knockout mice also exhibit a decrease in ErbB2 transgene expression levels, and an associated decrease in the expression of phospho-Akt, which may be associated with an increase in transgene silencing with age. It is proposed that cIAP2 knockout tumours have circumvented the absence of this survival gene in part by signaling angiogenesis, but the exact mechanism driving tumour formation remains unclear. In the second part of this study, mouse mammary epithelial stem and progenitor cells from dissociated mammary glands of NF-kappaB EGFP reporter mice were analyzed for NF-kappaB expression by flow cytometry and by fluorescent staining for nuclear p65 (NF-kappaB). Mouse mammary repopulating units (MRUs) and mammary colony forming cells (Ma-CFCs) were analyzed; these cell types have been previously described. MRUs have been characterized as basal-like mammary cells, and Ma-CFCs express markers characteristic of luminal mammary cells. It was found that only 6% of MRUs exhibited NF-kappaB expression, whereas 100% of the Ma-CFCs contained NF-kappaB expression. Analysis of tumours from MMTV-ErbB2 mice expressing the NF-kappaB EGFP reporter transgene was also completed. Sorting MMTV-ErbB2 induced mammary tumour cells based on CD44 surface staining (a previously reported tumour initiating cell marker) was unsuccessful, suggesting that CD44 may not be a putative marker for the cancer stem cell. These data suggest that NF-kappaB is activated during differentiation in the luminal Ma-CFC progenitor population, but not in the stem cell enriched populations.
Keywords: Biology, Molecular.